44 KRUPPEL-LIKE FACTOR 4 REGULATES ENDOTHELIAL INFLAMMATION. (1st March 2007) - Hamik, A.; Lin, Z.; Kumar, A.; Balcells, M.; Sinha, S.; Katz, J.; Gerzsten, R. E.; Edelman, E. R.; Jain, M. K.
Abstract : Background: The vascular endothelium plays a critical role in vascular homeostasis. A limited proinflammatory, prothrombotic state is appropriate in the context of infection or wound healing, but sustained endothelial activation leads to deleterious conditions such as atherosclerosis and pathologic thrombosis. Inflammatory cytokines and nonlaminar blood flow induce endothelial dysfunction and confer a proadhesive and prothrombotic phenotype. Therefore, identification of factors that mediate the effects of these stimuli on endothelial function is of considerable interest. Kruppel-like factors (KLFs) are a subclass of the zinc-finger family of transcription factors. Previous studies demonstrate that KLF proteins typically regulate critical aspects of cellular differentiation and tissue development. Studies from our laboratory and others demonstrate an emerging role for this family of transcriptional regulators in vascular biology. KLF4/GKLF (gut-enriched Kruppel-like factor) was first identified as being highly expressed in epithelial cells, and subsequent work has verified a critical role in skin and intestinal development. KLF4 has also been identified in endothelial cells, yet its function in vessel biology has yet to be elucidated. Methods and Results: Immunohistochemical analysis of mouse and human vascular tissues demonstrates the expression, in vivo, of KLF4 in human and mouse endothelial cells. Northern blot analysis of total mRNA harvested from primary endothelial cell lines derived from various human arterial vascular beds (aorta, pulmonary artery, and umbilical artery) shows expression of endothelial KLF4 in a variety of arterial and venous cell lines. Furthermore, we demonstrate that endothelial KLF4 is induced by proinflammatory stimuli and shear stress. Overexpression of KLF4 induces expression of multiple anti-inflammatory and antithrombotic factors, including eNOS and thrombomodulin, and inhibits basal and cytokine-mediated expression of a diverse set of proinflammatory factors, including MCP-1, RANTES, CRP, PAI-1, IL-6, and IL-8. The significance of endogenous expression of KLF4 on target genes was assessed in experiments using siRNA-mediated knockdown of KLF4. These experiments demonstrate that KLF4 depletion leads to enhancement of TNF-α-induced VCAM-1 and tissue factor expression. In addition to the determination of target genes, we have verified the functional importance of KLF4 by demonstrating that KLF4 expression markedly decreases inflammatory cell adhesion to the endothelial surface and prolongs clotting time under inflammatory states. As a first step toward understanding the molecular basis of KLF4-mediated regulation of endothelial target genes, we assessed the effect of KLF4 on target gene promoters. KLF4 differentially regulates the promoter activity of pro- and anti-inflammatory genes in a manner consistent with its anti-inflammatory function. Conclusion: Inflammatory cytokines and the biomechanical effects of laminar shear stress are the most potent effectors of endothelial homeostasis identified to date. Perturbation of endothelial function by proinflammatory cytokines or nonlaminar flow has been documented in most vascular disease states, including vasculitis, aneurysm formation, pathologic thrombosis, and atherosclerosis. The observations described above implicate KLF4 as a novel regulator of endothelial activation in response to proinflammatory stimuli. A greater understanding of KLF4 function is thus of considerable scientific and potentially therapeutic interest.